A COMPARATIVE STUDY OF CONJUNCTIVAL AUTOGRAFT AND BARE SCLERA TECHNIQUES IN THE TREATMENT OF PTERYGIUM - IDRIS, M. MUHAMMAD; DIVYA, N.; VEERAMANI, V. PANIMALAR A.; BHASKARAN, BINDU (International Journal of Current Pharmaceutical Research, 2020)
Objective: Pterygium is a fibrovascular growth encroaching from the conjunctiva into the cornea. This study deals with the comparison of conjunctival autograft and bare sclera technique as treatment options for pterygium. Methods: This study was done in the ophthalmology department of Saveetha Medical College, Thandalam, Chennai. A total of 100 patients were diagnosed of pterygium was taken for the study, out of which 60 patients were operated on with conjunctival autograft and 40 patients were operated with bare sclera technique. Patients with hypertension, diabetes mellitus were excluded. Post-operative complications and recurrence were noted. All the patients were between the age group of 20-65 y. Results: The mean age of patients operated with conjunctival autograft was 43.6, whereas in bare sclera technique was 46.625. The maximum age was 63 and the minimum age was 23 in conjunctival autograft whereas in bare sclera technique, the maximum age was 64 and the minimum age was 22. The recurrence rate of pterygium in conjunctival autograft was 1 and the recurrence rate of pterygium in bare sclera technique was 4. Conclusion: The present study revealed that conjunctival autograft was a better treatment option compared to the bare sclera technique for excision of pterygium